1998
DOI: 10.1136/jcp.51.6.467
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Le Lamentin (alpha 20 (B1) His-->Gln) in a British family: identification by electrospray mass spectrometry.

Abstract: The first identification of haemoglobin Le Lamentin ( 20 (B 1 ) His → Gln) in a British patient is described. The patient was a 69 year old asymptomatic white male being screened for diabetes, whose blood was undergoing its first ever analysis for glycated haemoglobin using a Glycomat II analyser. Identification of the haemoglobin variant was by electrospray mass spectrometry. (J Clin Pathol 1998;51:467-470)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…(2003). However, we agree with the reported statement (Reynolds et al. , 2002) that considerable expertise is needed for the interpretation of mass spectra.…”
Section: Discussionsupporting
confidence: 92%
“…(2003). However, we agree with the reported statement (Reynolds et al. , 2002) that considerable expertise is needed for the interpretation of mass spectra.…”
Section: Discussionsupporting
confidence: 92%
“…Since the histidine to glutamine substitution at codon 20 in Hb Le Lamentin is reported to be present in an external residue of the hemoglobin molecule, it is not known to cause any change in the physiological function of the hemoglobin. This variant has been previously reported in a black family in French West Indies (Martinique) [6], and Spanish [3], Japanese [7] and British families [5,8]. This is the first report of this rare variant in Indian population.…”
Section: Resultssupporting
confidence: 53%
“…4 Using a similar technique for HbA 1c , we have also found a case in the UK. The patient is a 46 year old diabetic woman with a plasma glucose of 11.2mmol/litre and HbA 1c of 5.5% (reference range, 3.8-5.5%), with a haemoglobin trace on a Menarini HA-8121 analyser that exhibited an unusual early eluting fraction.…”
mentioning
confidence: 66%
“…Therefore, we subjected the blood sample to electrospray ionisation tandem mass spectrometry, as described previously. 4 This revealed that the patient was heterozygous for the Le Lamentin mutation involving substitution of histidine by glutamine at position 20 on one of the -chains of haemoglobin. Although the patient's family is based in the north west of England, she says there is a link with Romany gypsies several generations ago, but we did not feel there was suYcient clinical justification for a detailed family study.…”
mentioning
confidence: 99%